Services marketing : integrating customer focus across the firm - Zeithaml, Valarie A.; Bitner, Mary Jo; Gremler, Dwayne D. (McGraw-Hill, 2013)
Focuses on knowledge needed to implement service strategies for competitive advantage across industries. This title introduces students to topics that include management and measurement of service quality, service recovery, the linking of customer measurement to performance measurement, service blueprinting, customer cocreation, and more